PENGEMBANGAN MEDIA PERMAINAN CATUR RANGKA MATERI SISTEM GERAK MANUSIA MUATAN IPA KELAS V SEKOLAH DASAR - Rachmadina Tri Kencana; Herlina Usman; Tunjungsari Sekaringtyas (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The use of media is one of the essential aspects of the learning process, because, it will provide a different and certainly more varied learning experience so that it will attract students and make it easier to understand the learning material. This research and development aims to produce a learning media to make it easier for students to understand learning material, especially on the material of  human locomotor organs system  in a fun way. Learning will be meaningful for students if the media used is the appropriate one. The methodology in this research is Research an Development (RND). The type of model used in the ASSURE development model, which consist of 6 stages including analyze learner; state objectives; select methods, media and materials; utilize media and materials; require learner participation; and evaluate and revise. The final results of this research produces a learning media that is useful to support the learning process on the material of human movement organs. The data collection technique used in this study was through observation, interviews, and questionnaires. This research was conducted only to the stage of expert validation to test the feasibility of the product. The product feasibility test involves 3 experts, namely media experts, material experts, and language experts. The results obtained from the three experts if the average is 4.5 from the maximum value of 5, or if converted in percentage is 90%, which means the media is included in the very good category. This shows that the framework of the chess game media is suitable for use in science learning material for human llocomotor organs system.